Pengabdian PENGABDIAN KEPADA MASYARAKAT DENGAN PELATIHAN MENULIS TEKS PUISI MELALUI STRATEGI PEMBELAJARAN BERBASIS PROYEK PADA SISWA KELAS X, SITINJAK: PENGABDIAN KEPADA MASYARAKAT DENGAN PELATIHAN MENULIS TEKS PUISI MELALUI STRATEGI PEMBELAJARAN BERBASIS PROYEK PADA SISWA KELAS X, SITINJAK - Elnila Caniago; Fita Delia Gultom; Parlindungan Siregar; Erni Rawati Sibuea; Riza Rahmadani; Dea Febriani Hasibuan (CV. Alfa Pustaka, 2026)
This community service activity was carried out with the aim of improving students' ability to write drama texts by producing products through project-based learning strategies. The material provided in the community service program introduced project-based learning strategies and the results of projects produced through active poetry writing. Project-based learning can improve students' psychomotor thinking skills in creating various scientific products containing poetry. From the results of the community service program carried out in Sitinjak, of the 40 students who were given project-based learning, 50%, or 20 students, were able to create scientific works of poetry in the form of a book containing a collection of poems of various genres. The community service program carried out in Sitinjak has a positive impact on 10th-grade high school students, providing an atmosphere that fosters a positive perspective on learning. Students are allowed to contribute creative and innovative ideas in creating their scientific works.